INTERPERSONAL FUNCTION IN HAMILTON LYRICS - Zahara, Mutia; Gintings, Immanuel Prasetya (Universitas Negeri Medan, 2019)
This study aimed at identifying the types of interpersonal function in Hamiton and focuses on Halliday and Matthiessen™s (2004) perspective of interpersonal function applied in Hamilton Lyrics. and how the interpersonal function realized in Hamilton Lyrics. This study was conducted by applying descriptive qualitative methode. The source of the data were taken from collected by watching streaming platforms such as Disney+ Hotstar, one of which is dedicated to Disney films. The technique for analyzing the data is qualitative research. The results of this research showed the classifying of data from Hamilton Lyrics selected song lyrics, also analyzing the mood structure regarding the most and residue. It was found there were 171 clauses in the Hamilton Lyrics, with the mood types and residue, 57 clauses were from the first lyrics in Hamilton Lyrics entitled Alexandre Hamilton, 80 clauses from the second in Hamilton Lyrics entitled Satisfied, and 34 clauses are from Hamilton Lyrics entitled You™ll Be Back. The classification are : 136 clauses of Declarative Mood, 27 clauses of Imperative Mood, and 8 clauses of Interrogative Mood. The researcher concluded that the analyzed and classified the Hamilton Lyrics based on the order of subject and finite to find the mood types and modality in each clause. The interpersonal function analysis was described and provided the examples of how that sentence categorized into the specific mood types and residue.